Interpreting conflicts and conflicts in interpreting: A micro-historical account of the interpreting activity in the Korean Armistice Negotiations - Wang, Binhua; Xu, Minhui (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2016)
The Korean Armistice Negotiations are among the major historical events shaping geopolitical situations in East Asia after World War II. While previous studies of the negotiations followed mainly the approach of traditional historical research, the present study offers a new perspective of the ‘neglected’ participants – the interpreters who worked for the series of negotiations. An analysis of “post-hoc accounts” of interpreters, using a micro-historical approach, demonstrates complexity of interpreting for wartime negotiations and reveals various conflicts in the interpreting of armistice negotiations as perceived by the interpreters. Intense conflicts were found in the interpreting activity, including: conflicts between the interpreters on both sides of the negotiations, hidden conflicts between the interpreters and their principals, conflicts between different interpreter roles, conflicts over language use between the two sides of the negotiations, and conflicts arising from misconceptions of the interpreting activity. It was also discovered that the interpreters in the armistice negotiations were generally loyal as the army soldiers instead of maintaining a neutral stance, such as is expected from professional interpreters nowadays. The micro-historical study of the interpreters’ accounts of the major historical events can be useful in exploring and explaining what is hidden behind the complexity of conflicts, thus offering a new approach to interpreting studies as well as to historical studies.